language and philosophy: an analysis of the turn to the subject in modern philosophy with historical linguistic approach - احمد حسینی (Journal of Philosophical Investigations, 2019)
One of the main characteristics of the philosophy of Descartes which marked the starting point of modern philosophy and was continued by English empiricism and German Idealism is a special attention to the subject instead of cosmos, being or God. But what caused such a turn to subject? With a historical linguistic approach it can be shown that the replacement of old languages of philosophy namely Greek, Arabic and Latin language by modern European languages namely French, English and German can be one of the causes of that turn in the history of philosophy. It seems interesting that the change in modern European language occurred exactly at the same time the modern philosophy appeared. In this research we will concentrate on the word order and the possibility of the omission of the subject in the sentence. In modern European languages there is a insistence on the subject to appear at the beginning of the sentence. This can lead to a special attention to the subject in philosophical aspect. It may seem interesting that old languages of philosophy are null-subject languages in the sense that in these languages the subject can be omitted. In these languages the subject sometimes comes after the verb or even will not appear in the phrase. That may seem why in those languages a philosophy similar to modern philosophy did not appear. Finally it will be shown that the change in language did not confine to mere language and has important philosophical implications.